Класична література крізь призму етно- та соціопсихології Олександра Кульчицького - Яблонська, Ольга; Yablonska, Olga (Східноєвропейський національний університет імені Лесі Українки, 2015)
У статті проаналізовано такі складники етно- та соціопсихології О. Кульчицького, як ідея преперсоналізму Г. Сковороди, архетипні іпостасі Т. Шевченка (Віщун - Борець - Мученик), проблеми провідника та національної спільноти в поемі І. Франка «Мойсей», психосоціальний аспект проблеми культу М. Шашкевича. . In the article it is analyzed the A. Kulchytsk's vision of the role of the leading figures of classical Ukrainian literature and laws of the history of local litersture in light of ethnopsychology. Study of researcher «"Soul of race" as a totem and the term» (1939), «Exisistentic concept of life and Ukrainian spirituality» (1948), «Heopsyhological aspect characterology of Ukrainian man» (1956) is considered as a landmark in the development of its ethno and sociopsychological systems views. In particular it is accented on G. Skovoroda's prepersonalizm idea of the A. Kulchytsky's concept. It is studied archetypal incarnation coverage scientist of Taras Shevchenko (Soothsayer - Wrestler - Martyr), problems of national and community leader in Franko's poem «Moses», psychosocial aspect of the problem worship M. Shashkevych. It is proved, that ethnopsychological coverage phenomena Ukrainian literary process is an important component of its etnomental model.
Classical Literature Through the Prism of Ethno and Sociopsychology of Alexander Kulchytsky
Keywords: етнопсихологія; культ письменника; ethnopsychology; cult writer